Women in early medieval Europe, 400 - 1100 - Bitel, Lisa M. (Cambridge medieval textbooks, 2002)
Gender and landscapes -- Invasions, migrations, and barbarian queens -- The theory and practice of religion -- Survival by kinship, marriage, and motherhood -- The take-off: mobility and economic opportunity -- Conclusion: concerning famous women before and after 1100